14=-(p-8)

Simple and best practice solution for 14=-(p-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14=-(p-8) equation:


Simplifying
14 = -1(p + -8)

Reorder the terms:
14 = -1(-8 + p)
14 = (-8 * -1 + p * -1)
14 = (8 + -1p)

Solving
14 = 8 + -1p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add 'p' to each side of the equation.
14 + p = 8 + -1p + p

Combine like terms: -1p + p = 0
14 + p = 8 + 0
14 + p = 8

Add '-14' to each side of the equation.
14 + -14 + p = 8 + -14

Combine like terms: 14 + -14 = 0
0 + p = 8 + -14
p = 8 + -14

Combine like terms: 8 + -14 = -6
p = -6

Simplifying
p = -6

 

See similar equations:

| -(7-4x)=9 | | -18-6k=6(1+3k) | | 5n+34=-2(1-7n) | | 2(4x-3)-8=4+2x | | 3n-5=-8(6+5n) | | -(1+7x)-6(-7-x)=36 | | -3(4x+3)+4(6x+1)=43 | | 24a-22=-4(1-6a) | | -5(1-5x)+5(-8x-2)=-4x-8x | | 29=7+x+x+2 | | 52=2(x+6)+2(9) | | 8a+7-14a= | | -6(1-2r)=42 | | 38=2(2) | | 3x+23= | | 5(4x-3)=25 | | -2(v+7)=-30 | | -8(8-7x)=-64 | | -3(p+7)=-18 | | 5(-2x-2)=70 | | 9(2x+5)+3x=75 | | -2(b-1)=4 | | -7+9k=1+8k | | 7(8x-8)=56 | | 8(-8+2x)=-16 | | Y=2x-1 | | 2(8a+5)=75 | | 2(8a+5)=74 | | 4(r-3)=-32 | | -5(8x+8)=-80 | | 11x+34y= | | 2(7k-5)=32 | | 4(4n+1)=36 | | -4(1-2x)=-44 | | 10-5p=-4+p+2-4p | | 7(8b-2)=-20 | | 7(8n-2)=-14 | | 2(8b-2)=-20 | | 4(5x-2)-6x=5(2x+4) | | 6=x+2 | | (y+3)(2y-1)=9 | | -3a+10=-11 | | 6(n-8)=-18 | | 10-2(3x+4)=11 | | 7+2c-4*4=-9 | | 15p+3(p-1)=3(2*2*2) | | 2x+30=7x | | 2k+6=5k-3 | | 3b-2=2b+1 | | 2(3n+7)=5n | | 5s-9=2(s-6) | | 1.4z+2.2=2.6z-0.2 | | -3(3x+5)=-5(2x-2) | | V+1=v-6 | | 3(x+4)=3x | | -2(8-3x)=6x+2 | | 5x+6=2x+15 | | 11(x-6)=-4-7 | | -3(x+1)-10=12+8 | | 22-42=4(x-1)-4 | | y+1=-3+4 | | 10=7t-12t | | 2p-5=4-3(p+2) | | 3x-7=4x+5 | | 12+x-3=21 |